Political theory in transition - O'Sullivan, Noël (Routledge, 2000)
During the past two decades there has been increasing dissatisfaction with established political categories, on the grounds that they no longer fit many of the facts of contemporary life, or adequately express many contemporary political ideals. Political Theory in Transition explores the principal reasons for this dissatisfaction and outlines some of the most influential responses to it. Key features of this textbook: * covers many of the important areas in political theory including: Communitarianism; Identity; Feminism; Liberalism; Citizenship; Democracy; Power; Authority; Legitimacy; Nationalism; Globalization; and the Environment * includes chapters written by some of the foremost authorities in the field of political theory * divided into four useful sections, beginning with the concept of the individual, and progressing to beyond the nation-state. During the past two decades there has been increasing dissatisfaction with established political categories, on the grounds that they no longer fit many of the facts of contemporary life, or adequately express many contemporary political ideals. Political Theory in Transition explores the principal reasons for this dissatisfaction and outlines some of the most influential responses to it. Key features of this textbook: * covers many of the important areas in political theory including: Communitarianism; Identity; Feminism; Liberalism; Citizenship; Democracy; Power; Authority; Legitimacy; Nationalism; Globalization; and the Environment * includes chapters written by some of the foremost authorities in the field of political theory * divided into four useful sections, beginning with the concept of the individual, and progressing to beyond the nation-state.
Keywords: Political science -- Philosophy.; Political culture.; State, The.; Citizenship.; État.; PHILOSOPHY -- Political.; Citizenship; Political culture; Political science -- Philosophy; State, The; Multi-User.